Painism: Some Moral Rules for the Civilized Experimenter - Ryder, Richard D. (Cambridge quarterly of healthcare ethics, 1999)
One of the barriers between ordinarily compassionate animal researchers and pro-animal ethicists is that the ethicists are usually seen as asking for far too much. They are perceived as demanding the complete abandonment of careers. In consequence, the ethicist is often ignored. Ethicists rarely give clear-cut rules to animal researchers as to how they can continue in animal research while at the same time adopting an increasingly moral approach. The purpose of this paper is to provide some rules to help the animals by aiding conscientious researchers who are not (yet) in a position to give up their careers entirely. These are ethical rules and not, therefore, in quite the same category as Russell and Burch's “three Rs” (replacement, refinement, and reduction) or the proposal that experimenters should seek proper training and retraining in animal care, and in the skills of euthanasia, anaesthesia, and analgesia. Nor are ethical rules quite the same as the requirement that all experimenters should acquaint themselves with the latest techniques for improving the animals' quality of life (such as the techniques of environmental enrichment, for example) or the need to keep themselves up to date in alternative research techniques that do not use animals. All these steps are of great importance and should be taken in addition to the ethical rules I propose.